SAT0159 Long-Term Follow-Up of Children Born to Mothers with Chronic Arthritides and Exposed in Utero to Anti-TNF-Alpha Agents: A Case-Control Study. (9th June 2015) - Agosti, M.; Andreoli, L.; Bazzani, C.; Nalli, C.; Reggia, R.; Gorla, R.; Taglietti, M.; Lojacono, A.; Motta, M.; Tincani, A.
Abstract : Background: Anti-TNFalfa agents have been used to control disease activity of patients with Chronic Arthritides (Rheumatoid Arthritis, Psoriatic Arthritis, Ankylosis Spondilitis) during the wash-out period of teratogenic drugs. Patients with flares during pregnancy may also receive anti-TNFalfa agents during the 2nd-3rd trimester. Objectives: To investigate the health and developmental conditions of children who were exposed in utero to anti-TNFalfa agents and to compare them with non-exposed children born to women with the same disease. Methods: An ad-hoc created questionnaire was submitted to women who were followed during pregnancy by a multidisciplinary team (rheumatologist, gynaecologist, neonatologist). Data on birth, lactation, weaning, growth parameters, developmental milestones, vaccinations and disease conditions were collected for the first 24 months of life. Results: The characteristics of 24 cases (9 male, 15 female) (20 exposed to etanercept, 3 to adalimumab, 1 to certolizumab) and 24 controls (12 M, 12 F) are reported in the table (median value, interquartile range). Eighteen children were exposed during the first trimester (discontinuation of anti-TNFalfa agent at positive pregnancy index), while six during the 2nd-3rd trimester (discontinuation at 34th-37th week). Both cases and controls underwent vaccinations without any severe complications. Vaccinations were protective. Only one child developed chicken-pox despite vaccination (exposure to etanercept in the 1st trimester, until the positive pregnancy index). Conclusions: No differences in birth parameters, congenital malformations, and developmental steps in the first 24 months of life were found between cases and controls. Growth parameters were within the curves of the general population. Cases received more vaccinations than controls. This may be due to the feeling by either parents or paediatricians that these children exposed to immunosuppressive agents could be more susceptible to infectious diseases. No relevant infectious diseases nor post-vaccine complications were noted in the 6 children exposed to anti-TNFalfa during the 2nd-3rd trimester of gestation. Neurodevelopmental problems were recorded in 2 children: an autism spectrum disorder in one male exposed to etanercept in the 2nd-3rd trimester and a language delay in a male control. Globally, the long-term follow-up of children supports the safety of use of anti-TNFalfa agents, either preconceptionally or during the 2nd-3rd trimester of pregnancy. References: Ostensen, M. (2014) Safety issues of biologics in pregnant patients with rheumatic diseases, Academy of Sciences, New York. Disclosure of Interest: None declared